Teacher’s attitudinal coherence and the personalized education - Vera Tapia, Marcela (2019)
The attitudes of teachers with training in personalized education and their coherence with regard to the constituent notes of the person, the singularity, autonomy and openness were studied, considering the pedagogical conception corresponding to personalized education. A descriptive approach was considered and the participants were 102 intentionally chosen teachers. The instrument was a scale of attitudes referred to the singularity, autonomy and openness. Content validity was obtained using the criterion of experts evaluated through Lawshe index. Reliability was obtained using Cronbach’s alpha. The results make it possible to accept the different hypotheses, as teachers are in a favorable above-median attitude in a significant proportion of 75% or more and in turn there is a significant relationship between the attitudinalcomponents regarding the construct of personalized education. The analysis of the results allows to appreciate that conceptual formulations concerning the constituent notes of the person are reflected in theattitudes of teachers.